2012
DOI: 10.1038/cr.2012.4
|View full text |Cite
|
Sign up to set email alerts
|

A human ESC model for MLL-AF4 leukemic fusion gene reveals an impaired early hematopoietic-endothelial specification

Abstract: The MLL-AF4 fusion gene is a hallmark genomic aberration in high-risk acute lymphoblastic leukemia in infants. Although it is well established that MLL-AF4 arises prenatally during human development, its effects on hematopoietic development in utero remain unexplored. We have created a human-specific cellular system to study early hemato-endothelial development in MLL-AF4-expressing human embryonic stem cells (hESCs). Functional studies, clonal analysis and gene expression profiling reveal that expression of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 48 publications
(95 reference statements)
2
61
1
Order By: Relevance
“…Most of our understanding of transformation by MLL-AF4 has come from murine models [2][3][4]26,27 and human stem cell systems. 1,[28][29][30][31][32][33] These have provided important insights into the likely mode of action of MLL-AF4, but the in vivo leukemias produced in these studies do not recapitulate the actual human disease phenotype and latency, and therefore MLL-AF4 leukemogenesis remains particularly difficult to model. This suggests that in order to develop a bona fide MLL-AF4 model by which to further understand the disease pathogenesis and to screen novel small-molecule compounds, additional oncogenic events such as FLT3 constitutive activation 8 or the derivative AF4-MLL seem to be required to develop ALL.…”
Section: Discussionmentioning
confidence: 99%
“…Most of our understanding of transformation by MLL-AF4 has come from murine models [2][3][4]26,27 and human stem cell systems. 1,[28][29][30][31][32][33] These have provided important insights into the likely mode of action of MLL-AF4, but the in vivo leukemias produced in these studies do not recapitulate the actual human disease phenotype and latency, and therefore MLL-AF4 leukemogenesis remains particularly difficult to model. This suggests that in order to develop a bona fide MLL-AF4 model by which to further understand the disease pathogenesis and to screen novel small-molecule compounds, additional oncogenic events such as FLT3 constitutive activation 8 or the derivative AF4-MLL seem to be required to develop ALL.…”
Section: Discussionmentioning
confidence: 99%
“…Along the way, the field of stem cell biology has naturally become an important research area covered by papers published in Cell Research [2]. For instance, in the past year of 2012, Cell Research has published a number of important papers related to the stem cell field, covering diverse aspects and topics such as induced pluripotent stem (iPS) cells [3][4][5][6][7], mechanistic studies of pluripotency and differentiation [8][9][10][11], modeling of human diseases using stem cell-based systems [6,12], direct reprogramming of somatic cells to other cell types without passing through an pluripotent intermediate [13][14][15][16], as well as neural crest stem cells [17] and cancer stem cells [18][19][20].…”
mentioning
confidence: 99%
“…Of these, 196 (61%) were upregulated and 127 (39%) downregulated in lenalidomide-treated AML cells, establishing a lenaledomide-specific transcriptomic signature. To get insights into the biological functions affected by differentially expressed genes, we used the Gorilla software, 30,31 and found that many significant biological processes predicted to be activated in the lenalidomide-treated AML cells were associated with “migration/motility/mobilization/chemotaxis” (Figure 6A). In contrast, exposure of CB-CD34 + HSPCs to lenalidomide did not affect such biological functions (Figure 6B).…”
Section: Resultsmentioning
confidence: 99%
“…Hierarchical clustering of genes was performed with the one minus correlation metric and the unweighted average distance. Only genes showing >1.5-fold change expression and p-value<0.05 were considered differentially expressed and were subjected to gene ontology (GO) term analysis using Gorilla 30,31 publicly available at http://cbl-gorilla.cs.technion.ac.il. Microarray data were deposited in the public Gene Expression Omnibus database, accession number GSE106748.…”
Section: Methodsmentioning
confidence: 99%